2014
DOI: 10.1002/2013jb010385
|View full text |Cite
|
Sign up to set email alerts
|

A search for evidence of secondary static stress triggering during the 1992 Mw7.3 Landers, California, earthquake sequence

Abstract: Key Points:• Weak but significant evidence for secondary static stress triggering • 27% of aftershocks receive more positive secondary stress than from main shocks • Secondary stress cannot explain most aftershocks in main shock stress shadows Abstract Secondary triggering of aftershocks is widely observed and often ascribed to secondary static stress transfer. However, small to moderate earthquakes are generally disregarded in estimates of Coulomb stress changes (ΔCFS), either because of source parameter unce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 81 publications
(148 reference statements)
2
63
0
Order By: Relevance
“…The response of the −ΔCFS seismicity in Region III (Figure h) is especially enigmatic: it shows an immediate increase at the time of the Ocotillo event, inconsistent with the simple CFS predictions, although this elevated rate then drops below the pre‐Ocotillo Omori prediction some 20 days after Ocotillo, which is indicative of a delayed stress shadow effect. These results suggest that considering individual receiver focal mechanisms does not improve our ability to evaluate the relationship between static stress and seismicity, which is consistent with previous studies (Cattania et al, ; Meier et al, ; Segou & Parsons, ).…”
Section: Coulomb Stress Modelingsupporting
confidence: 90%
See 1 more Smart Citation
“…The response of the −ΔCFS seismicity in Region III (Figure h) is especially enigmatic: it shows an immediate increase at the time of the Ocotillo event, inconsistent with the simple CFS predictions, although this elevated rate then drops below the pre‐Ocotillo Omori prediction some 20 days after Ocotillo, which is indicative of a delayed stress shadow effect. These results suggest that considering individual receiver focal mechanisms does not improve our ability to evaluate the relationship between static stress and seismicity, which is consistent with previous studies (Cattania et al, ; Meier et al, ; Segou & Parsons, ).…”
Section: Coulomb Stress Modelingsupporting
confidence: 90%
“…We find that separation of events based on the sign of the ΔCFS when computed on their focal plane solutions does not significantly improve the correlation of seismicity rate changes and the sign of the calculated static stress change in Region III. This is consistent with Meier et al () who found that the sign of ΔCFS is often flipped when the static stresses are computed on nodal planes of focal mechanisms that have been randomly perturbed within their errors. This suggests that considering focal mechanism uncertainty will not improve any subdivision of an event distribution based on the sign of the ΔCFS.…”
Section: Discussionmentioning
confidence: 99%
“…These uncertainties include the finite fault model, earthquake distribution, focal depth, and focal mechanism solutions. The nodal plane uncertainties add random noise to the stress change estimates and systematically reduce a potentially large coulomb index [11]. It is difficult to perfectly explain the complex geological phenomenon by only the coulomb stress triggering hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Coulomb stress triggering of moderate-to-large earthquakes has been observed in the US [4,[11][12][13], in Europe [14][15][16], on the Sunda Trench [17][18][19], and in Japan [20][21][22][23][24][25]. However, in South America and Ecuador, the stress triggering theory has yet to be extensively studied [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…However, if other independent constraints on either of the two parameters are available, they can be combined with the estimates in much the same way that we combine estimates from multiple stations (equation 5). There are numerous candidate constraints that could be used in this sense: parameter estimates from other EEW algorithms that run in parallel, distance estimates from a real-time location algorithm (e.g., based on the concept of not-yet-arrived data; Zhou, 1994;Cua and Heaton, 2007;Satriano et al, 2008), S-P onset times t S−P , the waveform-based distance estimation method of Odaka et al (2003), or distance priors from seismicity observations (e.g., Kagan and Knopoff, 1981;Meier et al, 2014) and from proximity to mapped faults. Because distance and magnitude uncertainties are inherently coupled, any constraint that reduces the distance uncertainty will also reduce magnitude uncertainties.…”
Section: Enhancing Magnitude Estimates With Additional Parameter Consmentioning
confidence: 99%